Hydrogen Atom Abstraction by High-Valent Fe(OH) versus Mn(OH) Porphyrinoid Complexes: Mechanistic Insights from Experimental and Computational Studies - Jan Paulo T. Zaragoza; Daniel C. Cummins; Maxime A. Siegler; Sam P. de Visser; David P. Goldberg; Muhammad Qadri Effendy Mubarak (American Chemical Society, 2024)
Inorg. Chem. 2019, 58, 24, 16761–16770